Strategic Responses and Organizational Adaptations of Some Manufacturing Companies During the Community Quarantine Due to COVID-19 Pandemic - Alexander S. Carrascal , Ira C. Valenzuela (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2022)
The COVID-19 pandemic crisis was abrupt, worldwide in scope, and its effect on individuals, organizations, and economies was devastating. Such crisis and emergency need appropriate and timely response. This paper intends to know how business firms responded to the challenges posed by the COVID-19 pandemic. Specifically, it aims to determine the strategies adopted by manufacturing companies, to mitigate the adverse impact of quarantine and lockdown. In view of this objective, a survey was conducted involving seventeen companies, operating in the Province of Cavite, which is a home for eight special economic zones. The study aims to gather information on how business organizations in the provincial level survived the crisis, and hopefully, use it as initial baseline data for formulating contingency plans for future occurrence of pandemics and healt h crises. The result showed that 71% of the companies adopted multiple strategies to alleviate the negative effects of the pandemic. Ninety-four percent (94%) of the firms persevered by implementing reduced workweek and scaled-down or “stayin” production operation; 47% enforced retrenchment in the form of reduction in cost, assets, product lines, and overhead; 59% introduced innovation in production processes to adapt to the pandemic situation; and 35% opted to discontinue the production of less essential products. The result implies that business resiliency depends on the readiness of the organization to handle a crisis and production activities can continue during pandemic without compromising the minimum health standards, provided, appropriate strategies and adaptation plans are implemented. In other words, companies need not shut down during lockdown.